Pendidikan untuk mewujudkan keadilan sosial dalam peluang belajar siswa di tengah kesenjangan ekonomi - Rosada, Septia; Khasanah, Nur (Jurnal Pendidikan Agama Islam, 2025)
Education plays a crucial role in creating social justice, particularly in ensuring equal access to learning amidst the economic inequality that remains a challenge in Indonesia. In addition to serving as a platform for transferring knowledge, education also serves to shape the character, social values, and personality of students. This research uses a qualitative approach with descriptive methods to explore the relationship between educational policies and learning practices that influence equal learning opportunities at various levels of education. Data were collected through a literature review of books, scientific journals, and policy documents related to social justice issues in education. The results indicate that increasing access to education, equalizing learning facilities and infrastructure, and strengthening teacher competencies in addressing the socioeconomic diversity of students are key factors in realizing educational equality. Therefore, education that is inclusive, equitable, and based on humanitarian values ​​is an essential foundation for building a society that upholds social justice.